Novel colorimetric films based on starch/polyvinyl alcohol incorporated with roselle anthocyanins for fish freshness monitoring. (August 2017) - Zhai, Xiaodong; Shi, Jiyong; Zou, Xiaobo; Wang, Sheng; Jiang, Caiping; Zhang, Junjun; Huang, Xiaowei; Zhang, Wen; Holmes, Mel
Abstract: Novel colorimetric films were developed for real-time monitoring of fish freshness based on starch/polyvinyl alcohol (SPVA) incorporated with roselle ( Hibiseus sabdariffa L.) anthocyanins (RACNs). Firstly, RACNs were extracted from roselle dehydrated calyxes. Secondly, SPVA aqueous solution was obtained with a mass rate of 2:1 (starch/PVA). Thirdly, the colorimetric films were fabricated by immobilizing 30, 60 and 120 mg RACNs/100 g starch into SPVA matrix with casting/solvent evaporation method. FTIR spectra of the colorimetric films showed that RACNs were successfully immobilized into the SPVA matrix. X-ray diffraction spectra and SEM micrographs indicated that the crystallinity of PVA was reduced during the film-forming process and the compatibility between starch and PVA was improved, owing to the presence of RACNs. The incorporation of RACNs led to a decrease of water content and tensile strength and an increase of elongation at break of the colorimetric films compared with the SPVA film. The color stability test showed that the colorimetric films were stable at refrigeration temperature and room temperature up to 14 days with relative color changes below than 5%. The colorimetric films with lower content of RACNs were found more sensitive towards ammonia. An application trial was conducted to monitor the freshness of silver carp ( Hypophthalmichthys molitrix ) at refrigeration temperature. The colorimetric films presented visible color changes over time due to a variety of basic volatile amines known as total volatile basic nitrogen (TVB-N). Hence, these colorimetric films can be used to monitor the real-time fish freshness for intelligent packaging. Graphical abstract: Highlights: Colorimetric films were developed by using roselle anthocyanins, starch and PVA. Roselle anthocyanins improved the compatibility between starch and PVA. The colorimetric films had good color stabilities within 14 days at 4 °C and 25 °C. The colorimetric film with fewer roselle anthocyanins was more sensitive to NH3 . The colorimetric films can be used to monitor the fish freshness at 4 °C.